PENINGKATAN KUALITAS DAN NILAI FES NIRA AREN DI DESA TARO TEGALLALANG MELALUI DIVERSIFIKASI PRODUK OLAHAN - D.A. Swastini; Y. Ramona; C.I.S. Arisanti (Buletin Udayana Mengabdi, 2018)
Sucrose, electrolyte, vitamin, as well as probiotic bacterial contents of palm juice (Arrenga pinnata Merr) areuseful for the maintenance of the healthiness of human body. Due to its low glycemic index, palm sugar issafe to consume and has high potential for use as an alternative companion sugar for diabetes mellituspatients. In Taro village, almost 90% of the people there manage palm sugar plantations, but their ability toprocess and distribute their products is still limited. This program of Science and technology for the Societyaims to improve the quality and value of FEs palm juice by applying revitalization and diversificationmethods. Revitalization was conducted by socializing pre and postharvest preparation techniques andprocedures and the outcomes were measured by questionnaires. Diversification methods were conductedthrough training and advisory preparation of isotonic and probiotic drinks, as well as production of sugarcrystal. The results of this socialization showed that there was an increase in average knowledge of farmersfrom 22.57% (before socialization) to 73.87% (after socialization). Product diversification did not onlyincrease the value of FEs palm juice, but also saved energy and time of processing. As the product wassupported by credible results of laboratory tests, this product is currently marketed in some touristdestinations, such as Tegallalang, Gianyar.